Which surgeon demographic factors influence postoperative complication rates after total knee arthroplasty at U.S. News and World Report top-ranked orthopedic hospitals? - Adam M. Gordon; Andrew R. Horn; Keith B. Diamond; Mitchell K. Ng; Matthew L. Magruder; Orry Erez (Arthroplasty, 2022)
Abstract Introduction Complication rates are used to evaluate surgical quality-of-care and determine health care reimbursements. The U.S. News & World Report (USNWR) hospital rankings are a highly-referenced source for top hospitals. The objective of this study was to determine the surgeon demographics of those practicing at USNWR Top Ranked Orthopedic Hospitals and if any influence complication rates after total knee arthroplasty (TKA). Methods The 2009–2013 USNWR ‘Orthopedic’ hospital rankings were identified. A database of TKA surgeons with postoperative complication rates was compiled utilizing publicly available data from the Centers for Medicare and Medicaid Services (2009–2013). Using an internet search algorithm, demographic data were collected for each surgeon and consisted of: fellowship training, years in practice, age, gender, practice setting, medical degree type, residency reputation, case volume, and geographic region of hospital. Logistic regression was used to assess the relationship between surgeon demographics and postoperative complication rates. A P value of < 0.008 was considered significant. Results From 2009 to 2013, 660 orthopedic surgeons performed TKA at 80 different USNWR Top-Ranked Hospitals. Mean TKA case volume was 172 (Range, 20–1323) and age of surgeon was 50.8 (Range, 32–77). A total of 372 (56.8%) completed an orthopedic surgery fellowship. Mean adjusted 30-day complication rate was 2.24% (Range, 1.2–4.5%). After adjustment, factors associated with increased complication rates were surgeon age ≤ 42 (OR 3.15; P = 0.007) and lower case volume (≤ 100 cases) (OR 2.52; P < 0.0001). Gender, hospital geographic region, completion of a fellowship, medical degree type, and residency reputation were not significant factors. Discussion Complication rates of total knee arthroplasty surgeons may be utilized by patients and hospitals to gauge quality of care. Certain surgeon factors may influence complication rates of surgeons performing TKA at USNWR Top Ranked Orthopedic Hospitals. Study Type Level III, retrospective observational study.